Experimental Acoustic Investigation of Rotor Noise Directivity and Decay in Multiple Configurations - Giovanni Fasulo; Giosuè Longobardo; Fabrizio De Gregorio; Mattia Barbarino (Aerospace)
In the framework of the MATIM project, an acoustic test campaign was conducted on a platform derived from a commercial-class quadcopter within the CIRA semi-anechoic chamber. A dedicated rotor rig allowed systematic measurements of thrust, torque, and shaft speed together with near- and far-field noise using ten calibrated 1/2-inch precision microphones. Three configurations were examined: an isolated rotor, the same rotor mounted on an aluminium quadcopter plate, and the full four-rotor assembly. The resulting data set, acquired over 3000–8000 rpm, documents the azimuthal directivity and radial decay of tonal and broadband noise while separating motor, propeller, and installation contributions. Analysis shows that a nearby rigid plate scatters part of the sound field towards frontal and oblique observers and produces a shielding effect in the rotor plane. The combined operation of four rotors further redistributes energy and broadens blade-passing frequency harmonics. The database is intended as a benchmark for aeroacoustics codes and for the development of reduced-order models.